Trends in the Chamelea Gallina Production from Molise Region (Adriatic Sea, Italy): A Ten-Year Survey (Global Journal of Science Frontier Research, 2014)
This study provides a qualitative and quantitative assessment of Chamelea gallina stock in the italian region Molise (Adriatic Sea) in 2003-2012 years. We investigated abundance, biomass and size distr ibution of Clams populations. Reported results showed biomass and abundance fluctuations in several years and at different investigated areas. The areas with greater fishable biomass are those near Trigno and Rio Vivo rivers, especially in 2010-2012 years. In Both areas, the Clams biomass and density amounts show strong seasonal and annual variations with no detectable seasonal equal trends in several years. In this study, concentrations of sub-commercial size individuals suggesting crowded conditions were never detected. Data analysis also evidence that fishery activity is based almost exclusively on specimens that have just reached minimum commercial size (25-35 mm). However, in both areas, there was a progressive increase in commercial Organisms size; so it is supposable, despite recruitment low rate, a positive trend for population growth.
Keywords: chamelea gallina; bivalves; size distribution; resource’s management; adriatic sea